6y+6z=-1

Simple and best practice solution for 6y+6z=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+6z=-1 equation:


Simplifying
6y + 6z = -1

Solving
6y + 6z = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6z' to each side of the equation.
6y + 6z + -6z = -1 + -6z

Combine like terms: 6z + -6z = 0
6y + 0 = -1 + -6z
6y = -1 + -6z

Divide each side by '6'.
y = -0.1666666667 + -1z

Simplifying
y = -0.1666666667 + -1z

See similar equations:

| .7(x-2)=3 | | 65=98 | | 4x+20y=3 | | X=1/180 | | y=f(x)+3 | | 5-3x=25 | | -2y-3(4-2Y)=2(y-3)+6 | | 2y+x(2-y)=9 | | 221=(4+x)(x) | | 7+2(2y-2)=-3(3y-6)+4y | | x=(-13) | | 6x+2x=180 | | 3y-5y=10 | | y=(1)/(3)f(x) | | 9x-4y=149 | | 40k÷1/5 | | 10x+2=44 | | 40÷1/5 | | 5x+(5x+43)+37= | | -3.4p+5.8-(7p+0.4)+5.8p= | | y=1/3f(x) | | 10x-6=2(5x-4) | | 2y+2-y=9 | | 3x-(x+5-1)+(x-x+4)= | | f^2+3f-70= | | X^2-6x+10=o | | (w*1)+(1-w)*11=3 | | 5-y-3y=27 | | f(x)=x^2-5x-150 | | x^2=56+x | | 11x+20=15x | | 6x^2+41x-7= |

Equations solver categories